2004
DOI: 10.1016/s0002-9440(10)63379-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lymphangiogenic Factors and Evidence of Intratumoral Lymphangiogenesis in Pancreatic Endocrine Tumors

Abstract: Lymphangiogenesis is thought to promote the progression of malignant tumors. Because the lymphangiogenic factors vascular endothelial factor (VEGF)-C and -D are expressed in endocrine cells, we investigated their expression in pancreatic endocrine tumors (PETs) and correlated these data and intratumoral lymph vessel density (iLVD) with clinicopathological features. Lymph vessels were identified with anti-podoplanin antiserum and with podoplanin/proliferating cell nuclear antigen double labeling. PETs (n ‫؍‬ 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
62
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 33 publications
11
62
1
3
Order By: Relevance
“…We found that intratumoral lymphatic vessels are present in colon cancer, using D2-40. Similar to previous studies, we found that most of intratumoral lymphatics are small and flattened, 23,32,34 contrasting the widely open lymphatics in peritumoral regions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that intratumoral lymphatic vessels are present in colon cancer, using D2-40. Similar to previous studies, we found that most of intratumoral lymphatics are small and flattened, 23,32,34 contrasting the widely open lymphatics in peritumoral regions.…”
Section: Discussionsupporting
confidence: 91%
“…23,24 However, Clarijs et al, 25 reported newly formed lymph vessels within the solid tumors using double staining with CD31 and PAL-E. Others have recently observed intratumoral lymphatics in melanomas, 26,27 breast, 28 head and neck, 29,30 pancreatic carcinoma, 31 and islet cell tumor. 32 A recent study detected intratumoral lymphatics in 91% of colorectal carcinoma. 33 Our results are in agreement with the later study.…”
Section: Discussionmentioning
confidence: 98%
“…The present study examined 85 specimens and proliferative lymphatics were detected in 25 (29%) with PF-L ranging from 0 to 2.2%. PF-L ranged from 0 to 3% in studies of other tumour types, [36,42,43]. The low PF-L is undoubtedly due to the inability of the methodology to accurately detect all dividing LECs within tumours, and is most probably underestimated as sprouting of new vessels begins at different levels along the lymphatic vessel [44].…”
Section: Discussionmentioning
confidence: 99%
“…2 In recent years, several markers specific for lymphatic endothelium, including vascular endothelial growth factor receptor-3 (VEGFR-3), the transmembrane proteins LYVE-1 and podoplanin, and the transcription factor Prox-1, have been used to evaluate intratumor lymphatic vessels in solid tumors, including breast cancer. [4][5][6] Intratumor lymphatic endothelial cells were shown to be capable of proliferation in some types of cancer, suggesting de novo lymphangiogenesis. 4,7 These studies also showed a correlation between lymphatic vessel density and nodal metastasis in some tumors, 8 but not in others.…”
mentioning
confidence: 99%